Práxis e experiência de classe nos grupos produtivos de economia solidária: construindo processos formativos emancipatórios na formação humana e profissional - Vieira, Mauro Rogério de Almeida (2023)
There are no ready-made recipes for emancipation; the emancipatory 'novelty' arises at the heart of the social movement. It is not possible to move towards social transformation based on a general, abstract proposal forged in settings where science divorces itself from life and relegates social praxis. The formation of a new subject is not being gestated in the school institution, nor solely through solidarity economy. The formation of a new subject takes place at the heart of the struggle of workers, based on their concrete praxis—productive, reproductive, political, and revolutionary praxis. To relegate social praxis is to disregard the uniqueness of social experiences. The experience of the working class in solidarity economy is fraught with contradictions, yet it possesses specificities capable of fostering unusual actions that may contain a power significant enough for social struggle. What we aim to achieve with this analysis is to present some elements that can help us understand how the shaping of professional education is marked by the struggle for the formation of the working class. This shaping can enable us to approach other ways of educating people based on the class experience facilitated by the integration, for example, of professional education with solidarity economy. The main problems to be analyzed in this research were: what are the consequences of the relationships between professional education and solidarity economy groups? What educational experiences can be drawn from relationships in solidarity economy that may contribute to an alternative experience within the school institution? How do the educational experiences manifest in the relationships between solidarity economy groups and IFRN/Mossoró? In what ways can the political-educational praxis of solidarity economy contribute to the political-educational praxis of IFRN/Mossoró? The dialectical and materialist conception of history has allowed us to establish a certain path; it is not a completely ready and definitive path, but a horizon in which concepts and practices served as the compass that assisted us in unfolding our inquiries. In this sense, we assert that it is through these experiences with the working class that education connects with popular aspirations and reconfigures its political praxis.